Formulation and optimization of polymeric nanoparticles loaded with riolozatrione: a promising nanoformulation with potential antiherpetic activity - Solís-Cruz Guadalupe Y.; Alvarez-Roman Rocío; Rivas-Galindo Verónica M.; Galindo-Rodríguez Sergio Arturo; Silva-Mares David A.; Marino-Martínez Iván A.; Escobar-Saucedo Magdalena; Pérez-López Luis A. (Acta Pharmaceutica)
Riolozatrione (RZ) is a diterpenoid compound isolated from a dichloromethane extract of the Jatropha dioica root. This compound has been shown to possess moderate antiherpetic activity in vitro. However, because of the poor solubility of this compound in aqueous vehicles, generating a stable formulation for potential use in the treatment of infection is challenging. The aim of this work was to optimize and physio-chemically characterize Eudragit® L100-55-based polymeric nanoparticles (NPs) loaded with RZ (NPR) for in vitro antiherpetic application. The NPs formulation was initially optimized using the dichloromethane extract of J. dioica, the major component of which was RZ. The optimized NPR formulation was stable, with a size of 263 nm, polydispersity index < 0.2, the zeta potential of –37 mV, and RZ encapsulation efficiency of 89 %. The NPR showed sustained release of RZ for 48 h with release percentages of 95 and 97 % at neutral and slightly acidic pH, respectively. Regarding in vitro antiherpetic activity, the optimized NPR showed a selectivity index for HSV-1 of ≈16 and for HSV-2 of 13.